2001
DOI: 10.1159/000050877
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Non-Insulin-Dependent Diabetes mellitus and the TNF-β NcoI Genotype as Predictive Factors in Proliferative Diabetic Retinopathy

Abstract: The object of the study was to investigate the share of the polymorphisms I/D ACE, endothelin 1 4127G/A and TNF-β NcoI in the susceptibility to proliferative diabetic retinopathy (PDR) in non-insulin-dependent diabetes mellitus (NIDDM). Genotypes were detected by polymerase chain reactions and determined in a set of 246 Caucasian NIDDM subjects with defined PDR status. The relevance of genotypes and clinical characteristics to the PDR occurrence was tested using multiple linear regression models and discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
10
1
1
Order By: Relevance
“…Many genetic studies have been reported on the association with the development of DR. For example, proposed genes are angiotensin-converting enzyme gene (15,16), plasminogen activator inhibitor-1 gene (17,18), tumor necrosis factor gene (19,20), aldose reductase gene (21,22), nitric oxide synthase gene (23,24), vascular endothelial growth factor gene (25,26), transforming growth factor-beta gene (27), methylenetetrahydrofolate reductase gene (28,29), fatty acid binding protein 2 gene (30) and so on. However, the linkage of these gene polymorphisms with DR is still controversial because some specific genotypes of genes are associated with a more rapid course of DR, whereas others do not increase the frequency of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Many genetic studies have been reported on the association with the development of DR. For example, proposed genes are angiotensin-converting enzyme gene (15,16), plasminogen activator inhibitor-1 gene (17,18), tumor necrosis factor gene (19,20), aldose reductase gene (21,22), nitric oxide synthase gene (23,24), vascular endothelial growth factor gene (25,26), transforming growth factor-beta gene (27), methylenetetrahydrofolate reductase gene (28,29), fatty acid binding protein 2 gene (30) and so on. However, the linkage of these gene polymorphisms with DR is still controversial because some specific genotypes of genes are associated with a more rapid course of DR, whereas others do not increase the frequency of DR.…”
Section: Discussionmentioning
confidence: 99%
“…However, why PDR unlike NPDR affects only a subgroup of patients despite the same glycemic control and diabetes duration remains elusive. In addition to conventional risk factors, many genetic studies [4][5][6][7][8][9][10][11] have suggested the contribution of genetic factors to DR.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymorphism (252A/G in intron 1 and 804C/A in exon 3) of the LTA gene has been identified as a major risk factor for myocardial infarction (MI) in Japanese individuals [22]. Although there have been few reports on the association of tumor necrosis factor allelic polymorphism with DR in Caucasian [6] and Indian populations [7], whether this is true for Japanese is currently unknown. We therefore conducted this study to clarify the relationship between polymorphisms 804C/A in exon 3 and 252A/G in intron 1 of the LTA gene as well as À308G/A TNF-a promoter variant and DR in Japanese patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Kontrol ve çalışma grubundaki tüm hastalar 18 yaşın üzerindeydi. Tip 1 DM tanısı ADA kriterlerine göre değerlendirildi [15]. Açlık kan şekeri düzeyinin 126 mg/dL' nin üstünde olan bireyler çalışma-ya dahil edildi.…”
Section: Gereç Ve Yöntemunclassified